Underwater Image Recovery Under the Nonuniform Optical Field Based on Polarimetric Imaging - Haofeng Hu; Lin Zhao; Xiaobo Li; Hui Wang; Tiegen Liu (IEEE Photonics Journal, 2018)
The underwater imaging could be severely degraded by the scattering media due the backscatter veiling and signal attenuation. Image recovery based on polarization information has shown its efficiency in improving the quality of image in scattering medium, but few of them considered the effect of nonuniform optical field on the image recovery. In this paper, we consider the condition of nonuniform optical field, and we propose a method of retrieving the objects radiance based on estimating the degree of polarization (DOP) and the intensity of backscatter at different positions of the image. The experimental results demonstrate that the quality of the underwater image can be effectively enhanced by this method. In addition, compared with the previous methods, the method proposed in this paper can maintain a better performance at different positions of the image, thanks to considering the DOP and intensity of backscatter as spatial variables instead of constants.